A Development of COMIDEAP Learning Model to Enhance Numerical Analysis Skills - Matchima, Kajita (Journal of Community Development Research (Humanities and Social Sciences); Vol 11 No 3 (2561): July-September 2018, 2018)
สถาบันระดับอุดมศึกษามุ่งผลิตบัณฑิตที่มีมาตรฐานผลการเรียนรู้ตามกรอบมาตรฐานคุณวุฒิระดับอุดมศึกษาแห่งชาติ รูปแบบการเรียนรู้ถือเป็นนวัตกรรมทางการศึกษาที่มีผลต่อการพัฒนาทักษะด้านต่างๆ ของบัณฑิต การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อพัฒนารูปแบบการเรียนรู้แบบ COMIDEAP ในการส่งเสริมทักษะการวิเคราะห์เชิงตัวเลข ทำการเปรียบเทียบผลสัมฤทธิ์ทักษะการวิเคราะห์เชิงตัวเลขของนักศึกษา รวมทั้งศึกษาความพึงพอใจของนักศึกษาต่อรูปแบบการเรียนรู้แบบ COMIDEAP เพื่อส่งเสริมทักษะการวิเคราะห์เชิงตัวเลขที่พัฒนาขึ้น กลุ่มเป้าหมาย ได้แก่ นักศึกษาสาขาวิชาสถิติประยุกต์ ชั้นปีที่ 1 ที่ลงทะเบียนเรียนในรายวิชาความน่าจะเป็นเบื้องต้นในภาคเรียนที่ 1 ปีการศึกษา 2560 เครื่องมือในการวิจัยประกอบด้วย 1) แผนการจัดกิจกรรมการเรียนรู้แบบ COMIDEAP 2) แบบวัดผลสัมฤทธิ์ทางการเรียนรายวิชาความน่าจะเป็นเบื้องต้น และ 3) แบบสำรวจความพึงพอใจของผู้เรียนต่อรูปแบบการเรียนรู้แบบ COMIDEAP ในการสอนรายวิชาความน่าจะเป็นเบื้องต้น      ผลการวิจัย พบว่า      1. รูปแบบการเรียนรู้แบบ COMIDEAP เพื่อส่งเสริมทักษะการวิเคราะห์เชิงตัวเลขที่สร้างขึ้น ได้รับการประเมินความเหมาะสมจากผู้ทรงคุณวุฒิในระดับมากที่สุด      2. คะแนนเฉลี่ยของผลสัมฤทธิ์ทางการเรียนของนักศึกษาหลังการเรียน โดยใช้รูปแบบการเรียนรู้แบบ COMIDEAP เพื่อส่งเสริมทักษะการวิเคราะห์เชิงตัวเลขสูงกว่าคะแนนเฉลี่ยก่อนเรียนอย่างมีนัยสำคัญทางสถิติที่ระดับ .05      3. ความพึงพอใจของนักศึกษาหลังจากการใช้รูปแบบการเรียนรู้แบบ COMIDEAP เพื่อส่งเสริมทักษะการวิเคราะห์เชิงตัวเลขโดยภาพรวมอยู่ในระดับมากที่สุด คำสำคัญ: รูปแบบการเรียนรู้ COMIDEAP  รูปแบบการเรียนรู้แบบร่วมมือ  ทักษะการวิเคราะห์เชิงตัวเลข      Higher education institutions instruct graduates in accordance with standardized learning outcomes as stated in Thai Qualifications Framework for Higher Education. This learning model is considered educationally innovative, aiming to develop graduates’ skills. To follow the framework, this study focuses on the development of the COMIDEAP learning model (Cooperative learning: Motivation, Information, Discussion, Explain, Application and Progress) to enhance graduates’ skills in the academic area of numerical analysis. In the study, numerical analysis skills of students were assessed and compared with their skills through the COMIDEAP learning model. The students’ satisfaction with their learning experience was also evaluated. The target group were the first-year students enrolling in the course Introduction to Probability in the academic year 2007. The research instruments were: 1) lesson plans for the subject; 2) pre- and post-learning achievement tests ; and 3) a satisfaction questionnaire completed by the students. The findings revealed that:      1. The quality assessment of the COMIDEAP learning model was a highly efficient learning model.      2. At the completion of the subject, the students’ post-test scores were higher than their pre-test scores at a significant level, p > .05.      3. The students had a high level of satisfaction with their learning experience and numerical analysis skill achievements based on the COMIDEAP learning model. Keywords : COMIDEAP Learning Model, Cooperative Learning, Numerical Analysis Skill